The PG-SGA outperforms the NRS 2002 for nutritional risk screening in cancer patients: a retrospective study from China - Chen, Xinqiao; Liu, Xiangliang; Ji, Wei; Zhao, Yixin; He, Yuwei; Liu, Yining; Li, Qiguang; Shi, Hanping; Cui, Jiuwei (Frontiers in Nutrition, 2023)
Abstract Background & Aims: As a chronic wasting disease, cancer can lead to metabolic and physiological changes in patients, resulting in severe malnutrition. Therefore, accurate assessment of nutritional status and adoption of scientifically sound nutritional interventions are of great importance for patients with cancer. This study aimed to assess the necessity of implementing the Nutrition Risk Screening 2002 (NRS 2002) tool in conjunction with the Patient-Generated Subjective Global Assessment (PG-SGA) in patients with cancer. Methods: This retrospective study collected the clinical data of cancer patients from November 2011 to December 2018 in the Department of Oncology, Cancer Center, First Hospital of Jilin University. The NRS 2002 and the PG-SGA were used as screening tools for malnutrition. Clinical characteristics and laboratory results were detected. Anthropometric indices including hand-grip strength (HGS), visceral fat area (VFA), calf circumstance (CC), and appendicular skeletal muscle mass index (ASMI) were also collected. The diagnostic results from the NRS 2002 were compared to the malnutrition diagnosis using the PG-SGA. Results: Of the 2645 patients included in this retrospective study, the nutritional risk was found in 1763 (66.6%) patients based on the PG-SGA, and in 240 (9.1%) patients based on the NRS 2002, respectively. Among the 240 patients evaluated by the NRS 2002 for risk of malnutrition, 230 were also assessed by the PG-SGA as malnourished. There were no significant differences observed in the clinical characteristics and laboratory parameters between the two groups. Conclusions: The PG-SGA is effective and had a higher positive rate in screening malnutrition for patients with cancer. The NRS 2002 is not necessary for patients who are to be assessed with the PG-SGA.